2021
DOI: 10.1088/1755-1315/720/1/012142
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Corrosion Resistance of the Material of Oil and Gas Equipment in Water-Salt Solutions by Changing the Electrochemical Parameters

Abstract: The high aggressiveness of process liquids associated with the presence of dissolved gases, mechanical impurities, salt ions, mineral acids and bases in them contributes to the destruction of oil and gas equipment. The main way to increase the corrosion resistance of the material of oil and gas equipment under the action of acidic components is the injection of a chemical reagent - a neutralizer. To study the effect of an electric field on production media, a method has been developed to control the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The paper [21] presents the results of research on the accelerated formation of zinc phosphate coatings with enhanced corrosion resistance on carbon steel by introducing α-zirconium phosphate was evaluated and found that α-zirconium phosphate (α-ZrP) is used as a new eco-friendly accelerator of phosphate coatings, and α-ZrP effectively increases phosphate efficiency, reduces the phosphate grain size, and forms a denser phosphate coating. The paper [22] presents the results of research on the effect of catholyte on the kinetics of corrosion was studied and revealed the dependence of the corrosion rate of carbon steel 09G2S on the concentration of the reagent alkali and catholyte at different pH values where a comparative assessment of the use of the most effective concentration of catholyte to increase the corrosion resistance of the material has been carried out. The paper [23] presents the results of research on the preparation of metal matrix nanocomposites using Fe as base material reinforced with Al 2 O 3 and doped with CeO 2 using the powder metallurgy technique.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The paper [21] presents the results of research on the accelerated formation of zinc phosphate coatings with enhanced corrosion resistance on carbon steel by introducing α-zirconium phosphate was evaluated and found that α-zirconium phosphate (α-ZrP) is used as a new eco-friendly accelerator of phosphate coatings, and α-ZrP effectively increases phosphate efficiency, reduces the phosphate grain size, and forms a denser phosphate coating. The paper [22] presents the results of research on the effect of catholyte on the kinetics of corrosion was studied and revealed the dependence of the corrosion rate of carbon steel 09G2S on the concentration of the reagent alkali and catholyte at different pH values where a comparative assessment of the use of the most effective concentration of catholyte to increase the corrosion resistance of the material has been carried out. The paper [23] presents the results of research on the preparation of metal matrix nanocomposites using Fe as base material reinforced with Al 2 O 3 and doped with CeO 2 using the powder metallurgy technique.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The anodization process consists in electrolytic formation of a protective active coating on the metal surface [1][2][3][4][5][6] and is used to create coatings on aluminum products and its alloys. If aluminium parts are immersed as an anode in an appropriate electrolyte, an oxide layer of aluminium Al2O3 is formed on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the corrosion protection of an oil pipeline depends largely on the value of the polarization potential of its surface, which, in turn, determines the kinetics of electrode reactions in soil electrolytes [1][2][3][4][5][6][7][8][9][10][11][12]. The cathodic protection method ensures a drastic decrease in the corrosion rate of the pipeline metal due to turning the protected surface into a non-destructive cathode.…”
Section: Introductionmentioning
confidence: 99%